Embodied Coloniality - Nezihat Bakar-Langeland (Kvinder, Køn & Forskning)
This comprehensive study examines the lived experiences of Muslim immigrant women in Norway, focusing mainly on the colonial wounds as a manifestation of the enduring impact of coloniality on daily lives. The research illuminates the profound influence of colonial legacies on social structures, cultural norms, and power dynamics through meticulous examination and analysis of in-depth interviews. The participants’ narratives, including Amal, Ayse, and Zahra, provide crucial insights into the challenges of marginalization, dehumanization, and the struggle to forge a coherent sense of self within a society shaped by colonial structures. This study underscores the normalization of dehumanization and sheds light on the constraints imposed by the majority society, resulting in feelings of non-relationality, suffocation, survival, resignation, and a loss of futurity. By addressing the intersection of coloniality, racism, and the lived experiences of Muslim minority women, this research offers valuable contributions to the academic discourse on decolonial feminist studies of affect, providing a nuanced understanding of the complex dynamics at play in contemporary Norway.